2018
DOI: 10.7759/cureus.2769
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Heparin Leads to Rectus Sheath Hematoma: A Rare Complication

Abstract: Rectus sheath hematoma (RSH) is a rare complication that usually occurs in patients receiving anticoagulation therapy. It can mimic an acute abdomen and be life-threatening. RSH can develop even with prophylactic dose of heparin. Early recognition is necessary to decrease morbidity and mortality. RSH should be considered in anticoagulated patients who develop sudden onset of abdominal pain. RSH is usually managed conservatively, but sometimes requires surgery. Patients who are taking antiplatelet require caref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Although its incidence is rare, certain studies have reported a high mortality rate of up to 25% with anticoagulant therapy (2,4,11,12). The etiology of RSH includes trauma, intensive muscle contractions, and iatrogenic and anticoagulant therapy (2,3,5,12,13). Anticoagulant therapy is one of the major risk factors of RSH (14).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although its incidence is rare, certain studies have reported a high mortality rate of up to 25% with anticoagulant therapy (2,4,11,12). The etiology of RSH includes trauma, intensive muscle contractions, and iatrogenic and anticoagulant therapy (2,3,5,12,13). Anticoagulant therapy is one of the major risk factors of RSH (14).…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation of SIEAH is abdominal pain (2,8,11,12), which can become aggravated with the patient's movements (2,3,5,8). The typical finding during physical examination is an abdominal mass, which does not cross the middle abdomen (2,3,5,7,8). Peritoneal signs, such as muscle guarding or rebounding pain, may be positive; therefore, the presentation can mimic that of acute abdominal syndrome (3,7,8,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations